Motivation Mediates Performance - Renita Napitupulu, Dian; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2024)
BPJS Ketenagakerjaan is (Social Security Administering Agency for Employment) is a public program that provides protection for workers to overcome certain socio-economic risks and its implementation uses a social insurance mechanism as a state institution engaged in the field of social insurance. BPJS Ketenagakerjaan, formerly known as PT Jamsostek (Persero), is the implementer of the labor social security law. This study aims to see the effect of Work Stress and Work Conflict on Employee Performance with Work Motivation as an Intervening Variable at BPJS Ketenagakerjaan Branch Offices throughout Medan Raya. The results of this study are as follows: Work Conflict has a positive and significant effect on Employee Performance with an original sample value of 0.351 and p values of 0.011. Work Conflict has a positive and significant effect on Work Motivation with an original sample value of 0.783 and p values of 0.000. Work Motivation has a positive and significant effect on Employee Performance with an original sample value of 0.481 and p values of 0.001. Work Stress has a positive and insignificant effect on Employee Performance with an original sample value of 0.084 and p values of 0.186. Work Stress has a positive and significant effect on Work Motivation with an original sample value of 0.164 and p values of 0.017. Work Conflict has a positive and significant effect on Employee Performance through Work Motivation with an original sample value of 0.377 and p values of 0.001. Work Stress has a positive and insignificant effect on Employee Performance through Work Motivation with an original sample value of 0.079 and p values of 0.050.